Negative active material, negative plate and battery
By optimizing the structure of silicon-carbon composite particles, the problems of volume expansion and low lithium ion diffusion coefficient of silicon-based materials in lithium-ion batteries are solved, and high-gram capacity, stability and fast charging capacity are improved.
Patent Information
- Application Number
- CN202411352903.6
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-09-26
- Publication Date
- 2025-01-14
- Estimated Expiration
- 2044-09-26
AI Technical Summary
The large volume expansion and low lithium ion diffusion coefficient of silicon-based materials in existing lithium-ion batteries lead to poor fast charging capabilities and poor cycle stability.
By making silicon and carbon into composite materials, the silicon content, closed-cell volume ratio and shell thickness in silicon carbon composite particles are controlled, the structure of silicon carbon composite particles is optimized, and its ionic conductivity and electronic conductivity are improved to ensure that in the battery The volume expansion is small during the cycle.
It is achieved to improve the structural stability of the negative electrode active material and the energy density of the battery, first-time Coulomb efficiency, rate performance and cycle stability while ensuring high gram capacity.
Smart Images

Figure CN119315005A_ABST
Abstract
Description
Technical Field
[0001] The present invention relates to the technical field of batteries, and in particular to a negative electrode active material, a negative electrode sheet comprising the negative electrode active material, and a battery comprising the negative electrode active material. Background Art
[0002] Lithium-ion batteries are widely used in consumer electronic devices, electric vehicles, energy storage power stations and other fields due to their small size, light weight and no memory effect. In the current commercial lithium-ion batteries, the negative electrode material is mainly graphite material, but the actual gram capacity of existing graphite materials is low (only about 360mAh / g) and is close to its theoretical limit (372mAh / g), and the development space is limited. Silicon-based materials have ultra-high theoretical specific capacity (4200mAh / g) and are one of the ideal materials to further improve the energy density of lithium-ion batteries. However, the existing silicon-based materials have a large volume expansion during the battery charging and discharging process, which can easily cause problems such as fast battery cycle decay and large volume change rate. At the same time, the lithium ion diffusion coefficient of silicon-based materials is low, which limits the fast charging capability of silicon-containing lithium-ion batteries. Summary of the invention
[0003] The purpose of the present invention is to overcome the above-mentioned problems existing in silicon-based materials in the prior art, and provide a negative electrode active material, a negative electrode sheet comprising the negative electrode active material, and a battery comprising the negative electrode active material. The negative electrode active material of the present invention has good ionic conductivity and electronic conductivity while ensuring a high gram capacity, and has high structural stability. The battery comprising the negative electrode active material of the present invention can take into account high energy density, first coulomb efficiency, rate performance and cycle stability.
[0004] In the related art, silicon-based materials have the problems of large volume expansion and low lithium ion diffusion coefficient. After extensive research, the inventors of the present invention found that by making silicon and carbon into composite materials and controlling the relationship between the silicon content in specific areas of the silicon-carbon composite particles, the volume proportion of closed pores and the thickness of the shell, the negative electrode active material can have high ion conductivity and electronic conductivity while ensuring a high gram capacity, and has good structural stability, so that the volume expansion is small during the battery cycle. The reasons may be:
[0005] First, since the formation of closed-pore structure in silicon-carbon composite particles is related to the deposition of silicon during their preparation, the volume of closed pores is related to the silicon content in the silicon-carbon composite particles. The silicon content in the silicon-carbon composite particles directly affects their volume expansion. Within a certain range, the more silicon content, the greater the volume expansion of the silicon-carbon composite particles. And the volume of closed pores can provide a certain buffer space for the expansion of silicon. Therefore, the volume expansion of silicon-carbon composite particles can be improved by adjusting the volume ratio of closed pores.
[0006] Second, setting a carbon-containing shell on the surface of the core of the silicon-carbon composite particles can significantly improve the electronic conductivity and ionic conductivity of the silicon-carbon composite particles. However, since the theoretical specific capacity of carbon materials is relatively low compared to silicon materials, it is necessary to control the thickness of the shell so that the silicon-carbon composite particles can balance the specific capacity, ionic conductivity, and electronic conductivity.
[0007] Third, only controlling the volume ratio of the closed pores and the thickness of the shell has limited improvement on the performance of the silicon-carbon composite particles. This is because setting a coating layer on the surface of the core of the silicon-carbon composite particles has a better improvement effect on the outer electronic conductivity and ionic conductivity of the silicon-carbon composite particles than on the inner side; this will cause the transmission rates of electrons and ions on the outer and inner sides of the silicon-carbon composite particles to be mismatched, thus affecting the overall ionic conductivity, electronic conductivity, and capacity performance of the negative electrode active material, and at the same time, it will also have an adverse effect on the volume expansion of the negative electrode active material. Therefore, on the premise of a specific volume ratio of the closed pores and the thickness of the shell, it is necessary to coordinately control the silicon content relationship in specific regions of the silicon-carbon composite particles; so that the transmission rates of electrons and ions in each region of the silicon-carbon composite particles are matched, and the volume expansion is balanced. Thereby improving the overall specific capacity performance, ionic conductivity, electronic conductivity, and structural stability of the negative electrode active material. Based on this, the inventors of the present invention have proposed the following solutions:
[0008] In the first aspect of the present invention, a negative electrode active material is provided. The negative electrode active material includes silicon-carbon composite particles; the silicon-carbon composite particles have closed pores, and the volume ratio of the closed pores is 4%-50%; the silicon-carbon composite particles have a core-shell structure, and the shell of the core-shell structure includes carbon elements, and the thickness of the shell is t, 0 < t ≤ 10 nm; the cross-section of the silicon-carbon composite particles has a first region and a second region, the content of silicon elements in the first region is c1, and the content of silicon elements in the second region is c2, 0.15 ≤ c2 / c1 ≤ 1.4; wherein, the perpendicular line of the tangent at any point on the edge of the cross-section has a size of L on the cross-section, and on the perpendicular line, the region at a distance of 0.001L - 0.1L from the edge of the cross-section constitutes the first region, and the region at a distance of 0.1L - 0.5L from the edge of the cross-section constitutes the second region.
[0009] In the second aspect of the present invention, a negative electrode sheet is provided. The negative electrode sheet includes the negative electrode active material described in the first aspect of the present invention.
[0010] In the third aspect of the present invention, a battery is provided. The battery includes the negative electrode active material described in the first aspect of the present invention and / or the negative electrode sheet described in the second aspect of the present invention.
[0011] Through the above technical solutions, the present invention has at least the following advantages compared with the prior art:
[0012] (1) The negative electrode active material of the present invention has good ionic conductivity and electronic conductivity while ensuring a high gram capacity;
[0013] (2) The negative electrode active material of the present invention has good structural stability and can maintain low volume expansion during the battery charge and discharge cycle;
[0014] (3) The battery of the present invention can take into account high energy density, initial coulombic efficiency, rate performance and cycle stability.
[0015] The endpoints and any values of the ranges disclosed in this article are not limited to the precise ranges or values, and these ranges or values should be understood to include values close to these ranges or values. For numerical ranges, the endpoint values of each range, the endpoint values of each range and the individual point values, and the individual point values can be combined with each other to obtain one or more new numerical ranges, which should be considered as specifically disclosed in this article. BRIEF DESCRIPTION OF THE DRAWINGS
[0016] Figure 1 FIG. 4 is a schematic cross-sectional view of a silicon-carbon composite particle in an example of the present invention.
[0017] Figure 2 Shown is a transmission electron microscope (TEM) image of silicon-carbon composite particles in an example of the present invention. DETAILED DESCRIPTION
[0018] The specific embodiments of the present invention are described in detail below. It should be understood that the specific embodiments described herein are only used to illustrate and explain the present invention, and are not used to limit the present invention.
[0019] In the first aspect of the present invention, a negative electrode active material is provided. The negative electrode active material may include silicon-carbon composite particles. The silicon-carbon composite particles may have closed pores, and the volume ratio of the closed pores may be 4%-50%, such as 4%, 5%, 10%, 20%, 30%, 40% or 50%. The silicon-carbon composite particles may have a core-shell structure. The shell of the core-shell structure may include carbon element. The thickness of the shell is t, 0 < t ≤ 10 nm, such as 0.1 nm, 0.5 nm, 1 nm, 2 nm, 3 nm, 4 nm, 5 nm, 6 nm, 7 nm, 8 nm, 9 nm or 10 nm. The cross-section of the silicon-carbon composite particles has a first region and a second region. The content of silicon element in the first region is c1, and the content of silicon element in the second region is c2, 0.15 ≤ c2 / c1 ≤ 1.4, such as 0.15, 0.2, 0.3, 0.4, 0.5, 0.6, 0.7, 0.8, 0.9, 1, 1.1, 1.2, 1.3 or 1.4. Wherein, the dimension of the perpendicular line of the tangent at any point on the edge of the cross-section on the cross-section is L. On the perpendicular line, the region with a distance of 0.001L - 0.1L from the edge of the cross-section constitutes the first region, and the region with a distance of 0.1L - 0.5L from the edge of the cross-section constitutes the second region. On the perpendicular line, the region with a distance of 0.1L from the edge of the cross-section belongs to the first region.
[0020] As Figure 1 Shown is a schematic cross-sectional view of silicon-carbon composite particles in an example of the present invention. It can be seen from the figure that the dimension of the perpendicular line of the tangent at any point on the edge of the cross-section on the cross-section is L. On the perpendicular line, the region with a distance of 0.001L - 0.1L from the edge 1 of the cross-section constitutes the first region 2, and the region with a distance of 0.1L - 0.5L from the edge 1 of the cross-section constitutes the second region 3.
[0021] In one example, 0.15 < c2 / c1 ≤ 1.25.
[0022] In one example, 0.23 < c2 / c1 ≤ 0.76.
[0023] When c2 / c1 is greater than 1.4, the silicon content in the second region located relatively inside the silicon-carbon composite particles is higher than that in the first region, which will cause the expansion stress of silicon to be mainly concentrated inside the silicon-carbon composite particles, being unfavorable for the buffer of the closed pores to the volume expansion of silicon, resulting in fragmentation of the negative electrode active material during the process of lithium deintercalation and insertion, thereby leading to a decrease in the cycle capacity retention rate of the battery.
[0024] In the present invention, the content of silicon in the first region and the content of silicon in the second region can be tested by conventional methods in the art, such as using an energy dispersive spectrometer (EDS), specifically as follows: the silicon-carbon composite particles are evenly mixed with a binder and a solvent and then coated on the surface of a metal sheet (such as a copper foil), and after drying (or the metal sheet containing the silicon-carbon composite particles), an argon ion cutting machine (such as a Japanese electronic IB-19530CP argon ion cross-section polisher) is used for processing, and the cut samples are quickly transferred to a scanning electron microscope sample chamber for observation, and at least 5 points on the first region and the second region are measured respectively through the EDS point scanning mode to obtain the silicon content of each point, and the average value is calculated.
[0025] In one example, the closed cells account for 5% to 49% of the volume.
[0026] In one example, the closed cells account for 11%-35% of the volume.
[0027] When the volume proportion of closed pores is small (for example, less than 4%), the volume of closed pores in the silicon-carbon composite particles is small, making it difficult to effectively buffer the volume expansion of silicon, resulting in a high thickness expansion rate of the battery during the cycle; and when the volume proportion of closed pores is large (for example, greater than 50%), the volume of closed pores in the silicon-carbon composite particles is large, resulting in a low energy density of the battery.
[0028] In the present invention, the volume of the closed pores refers to the ratio of the volume of the closed pores to the volume of the silicon-carbon composite particles. The volume of the closed pores can be calculated by the following formula: Volume of closed pores = 1-g / (2.33-0.02×c), where g is the true density of the silicon-carbon composite particles, in g / cm 3 , c is the mass content of silicon element in the silicon-carbon composite particles.
[0029] In one example, 0.2 nm ≤ t ≤ 10 nm.
[0030] In one example, 1 nm≤t≤8 nm.
[0031] The shell containing carbon elements can improve the electronic conductivity of the silicon-carbon composite particles. However, when the thickness of the shell is too thick (for example, greater than 10nm), the mass of the shell accounts for a large proportion, which will cause the gram capacity of the silicon-carbon composite particles to be low, thereby causing the energy density of the battery to be low.
[0032] In the present invention, the thickness of the shell can be tested by conventional methods in the art, such as using TEM, specifically as follows: using a JEM-F200 field emission transmission electron microscope produced by JEOL Ltd., at least 10 sites are selected on the surface of the silicon-carbon composite particles, the thickness of the shell at each site is measured, and the average value is taken.
[0033] In the present invention, the content c1 of silicon in the first region may be 30%-75%, for example, 30%, 30%, 40%, 50%, 60%, 70% or 75%.
[0034] In one example, the content c1 of silicon in the first region is 31%-71%.
[0035] In one example, the content c1 of silicon in the first region is 38%-66%.
[0036] In the present invention, the content c2 of silicon in the second region may be 5%-60%, for example, 5%, 10%, 20%, 30%, 40%, 50%, 55% or 60%.
[0037] In one example, the content c2 of silicon in the second region is 6%-55%.
[0038] In one example, the content c2 of silicon in the second region is 9%-50%.
[0039] In the present invention, the mass content of silicon in the silicon-carbon composite particles may be 20%-65%, for example, 20%, 30%, 40%, 50% or 60%.
[0040] In one example, the mass content of silicon in the silicon-carbon composite particles is 21%-64%.
[0041] In one example, the mass content of silicon in the silicon-carbon composite particles is 25%-60%.
[0042] When the mass content of silicon in the silicon-carbon composite particles is small (for example, less than 20%), the gram capacity of the silicon-carbon composite particles is low, which will result in a low energy density of the battery; and when the mass content of silicon in the silicon-carbon composite particles is large (for example, greater than 65%), the volume of the closed pores cannot effectively alleviate the volume expansion of silicon, resulting in poor structural stability of the silicon-carbon composite particles, thereby affecting the battery's cycle capacity retention rate and thickness expansion rate.
[0043] In the present invention, the mass content of silicon in the silicon-carbon composite particles can be obtained by testing by conventional methods in the art, such as testing by thermogravimetric analysis, specifically as follows: using Shimadzu DTG-60 thermogravimetric analyzer for testing, testing conditions: sample amount 5 mg, air as atmosphere, heating rate of 10°C / min, from room temperature to 900°C and constant temperature for 40 minutes. The mass content of silicon in the silicon-carbon composite particles is c=7z / 15, where z is the final weight residual percentage of the test.
[0044] like Figure 2The TEM image of the silicon-carbon composite particles in one example of the present invention is shown. It can be seen from the image that the core and surface layer of the composite particles are both amorphous, and the thickness of the surface layer is about 3nm-5nm.
[0045] In the present invention, the core of the core-shell structure may include carbon and silicon.
[0046] In one example, the core includes porous carbon and silicon material located in the pores of the porous carbon.
[0047] In one example, the shell includes amorphous carbon.
[0048] In the present invention, the silicon-carbon composite particles may include at least one of nitrogen, phosphorus and sulfur.
[0049] Since nitrogen, phosphorus and sulfur are more electronegative than carbon, they are more likely to react with lithium. When at least one of nitrogen, phosphorus and sulfur is introduced into the silicon-carbon composite particles, the Li + The reaction energy barrier embedded in the silicon-carbon composite particles makes it easier for lithium ions to migrate in the silicon-carbon composite particles, which is beneficial to improving the ionic conductivity of the negative electrode active material.
[0050] In one example, the silicon-carbon composite particles include nitrogen, phosphorus, and sulfur.
[0051] In the present invention, the sum of the contents of nitrogen, phosphorus and sulfur in the silicon-carbon composite particles can be 15ppm-1000ppm, for example, 15ppm, 20ppm, 30ppm, 40ppm, 50ppm, 60ppm, 70ppm, 80ppm, 90ppm, 100ppm, 200ppm, 300ppm, 400ppm, 500ppm, 600ppm, 700ppm, 800ppm, 900ppm or 1000ppm.
[0052] In one example, the total content of nitrogen, phosphorus and sulfur in the silicon-carbon composite particles is 30 ppm-500 ppm.
[0053] When the sum of the contents of nitrogen, phosphorus and sulfur in the silicon-carbon composite particles is too small (e.g., less than 15 ppm), the ionic conductivity of the negative electrode active material cannot be effectively improved; and when the sum of the contents of nitrogen, phosphorus and sulfur in the silicon-carbon composite particles is too large (e.g., greater than 1000 ppm), the gram capacity of the negative electrode active material will be reduced, resulting in a decrease in the first coulomb efficiency and energy density of the battery. When the sum of the contents of nitrogen, phosphorus and sulfur in the silicon-carbon composite particles is within a specific range, the negative electrode active material has a higher lithium ion diffusion coefficient, which can improve the rapid discharge capability of the battery.
[0054] In the present invention, the contents of nitrogen, nitrogen and sulfur in the silicon-carbon composite particles can be obtained by conventional methods in the art, and the contents of nitrogen and sulfur can be obtained by, for example, elemental analyzer testing. The content of phosphorus can be obtained by, for example, inductively coupled plasma atomic emission spectroscopy (ICP-AES) testing.
[0055] In the present invention, the particle sizes Dv90 and Dv10 of the silicon-carbon composite particles satisfy 5 μm≤Dv90-Dv10≤25 μm, for example, 5 μm, 10 μm, 15 μm, 20 μm or 25 μm.
[0056] In one example, 7 μm ≤ Dv90 - Dv10 ≤ 24 μm.
[0057] In one example, 7 μm ≤ Dv90 - Dv10 ≤ 18 μm.
[0058] The difference between Dv90 and Dv10 can reflect the particle size distribution concentration of silicon-carbon composite particles. When the difference between the two is small (for example, less than 5 μm), it means that most of the particles in the silicon-carbon composite particles have similar particle sizes, which will reduce the packing density of the silicon-carbon composite particles, thereby reducing the volume energy density of the battery; when the difference between the two is large (for example, greater than 25 μm), it means that there are more particles with smaller particle sizes in the silicon-carbon composite particles, which will make the specific surface area of the silicon-carbon composite particles larger. During the first charge and discharge process of the battery, there are more side reactions between the negative electrode active material and the electrolyte, thereby reducing the first coulomb efficiency of the battery; or when the difference between the two is large, it means that there are more particles with larger particle sizes in the silicon-carbon composite particles, which will affect the processing performance of the negative electrode active material; in the preparation process of the battery, silicon-carbon composite particles with larger particle sizes are easily screened out, resulting in a lower volume energy density of the battery. When the difference between the two is within a specific range, it is beneficial to improve the first coulomb efficiency and volume energy density of the battery.
[0059] In the present invention, the particle size Dv10 and Dv90 of the silicon-carbon composite particles can be tested by conventional methods in the art, such as a laser particle size test method, specifically as follows: using a Malvern particle size tester for measurement, the test steps are as follows: the silicon-carbon composite particles are dispersed in deionized water containing a dispersant (such as nonylphenol polyoxyethylene ether) (the mass content of the dispersant is 0.02%-0.03%), ultrasonicated for 2 minutes, and then placed in a Malvern particle size tester for testing.
[0060] In the present invention, Dv10 may be 1 μm-6 μm, for example, 1 μm, 2 μm, 3 μm, 4 μm, 5 μm or 6 μm.
[0061] In one example, Dv10 is 2 μm-6 μm.
[0062] In one example, Dv10 is 2 μm-5 μm.
[0063] In the present invention, Dv90 may be 10 μm-30 μm, for example, 10 μm, 15 μm, 20 μm, 25 μm or 30 μm.
[0064] In one example, Dv90 is 12 μm-30 μm.
[0065] In one example, Dv90 is 12 μm-20 μm.
[0066] In the present invention, the oil absorption value of the silicon-carbon composite particles can be 10ml / 100g-100ml / 100g, for example, 10ml / 100g, 20ml / 100g, 30ml / 100g, 40ml / 100g, 50ml / 100g, 60ml / 100g, 70ml / 100g, 80ml / 100g, 90ml / 100g or 100ml / 100g.
[0067] In one example, the oil absorption value of the silicon-carbon composite particles is 31 ml / 100 g-79 ml / 100 g.
[0068] The oil absorption value can reflect the volume of stacked pores formed after the silicon-carbon composite particles are stacked. When the oil absorption value of the silicon-carbon composite particles is small (for example, less than 10ml / 100g), the volume of pores formed after the silicon-carbon composite particles are stacked is small, indicating that the negative electrode sheet containing the silicon-carbon composite particles has poor electrolyte retention ability, which will reduce the battery's cycle capacity retention rate; and when the oil absorption value of the silicon-carbon composite particles is large (for example, greater than 100ml / 100g), the volume of pores formed after the silicon-carbon composite particles are stacked is large, indicating that the negative electrode sheet containing the silicon-carbon composite particles has a high porosity, which will reduce the battery's volume energy density. When the oil absorption value of the silicon-carbon composite particles is within a specific range, the battery can take into account both a high cycle capacity retention rate and a high volume energy density.
[0069] In the present invention, the oil absorption value of the silicon-carbon composite particles can be tested by the following method, for example: weigh the mass of a clean beaker and a glass rod as m1, add 5 g of silicon-carbon composite particles thereto and record the total mass as m2, add dioctyl phthalate (DOP) dropwise with a titration bottle, weigh the total weight of the beaker at this time as m3, and the oil absorption value of the silicon-carbon composite particles = (m3-m2) / (m2-m1)×100.
[0070] In the present invention, the silicon-carbon composite particles may further include lithium element.
[0071] During the production or use of silicon-carbon composite particles, they may come into contact with air or water, so that the silicon-carbon composite particles contain oxygen. At this time, if the silicon-carbon composite particles contain lithium, the lithium will combine with the oxygen in the silicon-carbon composite particles, so that the oxygen will no longer react with the lithium in the electrolyte during the first charge and discharge process of the battery, thereby improving the first coulomb efficiency of the battery.
[0072] In the present invention, the content of lithium in the silicon-carbon composite particles can be 0.1%-20%; for example, 0.1%, 0.5%, 1%, 2%, 3%, 4%, 5%, 6%, 7%, 8%, 9%, 10%, 11%, 12%, 13%, 14%, 15%, 16%, 17%, 18%, 19% or 20%.
[0073] In one example, the content of lithium in the silicon-carbon composite particles is 1%-5%.
[0074] When the lithium content in the silicon-carbon composite particles is large (for example, greater than 20%), lithium that is not combined with oxygen elements is likely to appear in the silicon-carbon composite particles. This part of lithium is active and can easily react with the solvent in the slurry and produce gas during the electrode preparation process. Therefore, it will deteriorate the processing performance of the negative electrode active material, which is not conducive to the energy density and cycle retention rate of the battery.
[0075] In the present invention, the content of lithium in the silicon-carbon composite particles can be measured by conventional methods in the art, such as using ICP-AES.
[0076] In the present invention, the thermogravimetric curve of the silicon-carbon composite particles in air atmosphere has a weight gain peak at 600°C-800°C.
[0077] The weight changes of silicon-carbon composite particles in different temperature ranges in the thermogravimetric test correspond to different thermal behaviors. For example, the weight loss in the range <400℃ usually comes from the volatilization of water in the material during the heating process, and the weight loss in the range >550℃ usually comes from the process of carbon materials reacting with oxygen in the air to generate CO2. The weight gain in the range >600℃ comes from the process of silicon in the silicon-carbon composite particles reacting with oxygen in the air to generate SiO2. There is a weight gain peak at 600℃-800℃, indicating that the shell of the silicon-carbon composite particles covers the core more completely, and the silicon in it is active, which makes the battery have a higher first coulomb efficiency.
[0078] In one embodiment, the thermogravimetric curve of the silicon-carbon composite particles in an air atmosphere has a weight gain rate of 0.1%-40% at 600°C-800°C, for example, 0.1%, 0.5%, 1%, 5%, 10%, 15%, 20%, 25%, 30%, 35% or 40%.
[0079] In one example, the thermogravimetric curve of the silicon-carbon composite particles in air atmosphere has a weight gain rate of 0.5%-24.8% at 600° C.-800° C.
[0080] Since SiO2 will react with lithium during the charge and discharge process of the battery, resulting in irreversible capacity loss, when the weight gain rate at 600℃-800℃ is within a specific range, it indicates that the active silicon in the silicon-carbon composite particles is well protected by the shell and is not oxidized to SiO2, and the thickness of the shell is not too thick at this time, so that the battery has a higher first coulombic efficiency and energy density.
[0081] In the present invention, the specific steps of the thermogravimetric test of the silicon-carbon composite particles are as follows: using a Shimadzu DTG-60 thermogravimetric analyzer, the test sample amount is 5 mg, the test atmosphere is air, the heating rate is 10°C / min, and the test range is room temperature-900°C.
[0082] In the present invention, the true density of the silicon-carbon composite particles can be 1.4 g / cm 3 -2.2g / cm 3 , for example 1.4 g / cm 3 , 1.5g / cm 3 , 1.6g / cm 3 , 1.7g / cm 3, 1.8g / cm 3 , 1.9g / cm 3 , 2g / cm 3 , 2.1g / cm 3 or 2.2g / cm 3 .
[0083] When the true density of the silicon-carbon composite particles is within a specific range, the silicon-carbon composite particles have an appropriate closed pore volume. 3 ), the closed-pore content of the silicon-carbon composite particles is too high, which can easily make the volume energy density of the battery low; and when the true density is large (for example, greater than 2.2g / cm 3 ), the closed-pore content of the silicon-carbon composite particles is too low to buffer the volume expansion of silicon, thereby affecting the thickness expansion rate of the battery.
[0084] In the present invention, the true density of the silicon-carbon composite particles can be tested by conventional methods in the art, such as the gas volume displacement method, as follows: use the JW-M100A fully automatic true density tester to test, the test gas is helium, and the test environment temperature is 25°C ± 2°C.
[0085] In the present invention, the particle size Dv50 of the silicon-carbon composite particles may be 6 μm-15 μm, for example, 6 μm, 7 μm, 8 μm, 9 μm, 10 μm, 11 μm, 12 μm, 13 μm, 14 μm or 15 μm.
[0086] In one example, the particle size Dv50 of the silicon-carbon composite particles is 7 μm-12 μm.
[0087] When the particle size Dv50 of the silicon-carbon composite particles is small (for example, less than 6μm), the average particle size of the silicon-carbon composite particles is small and the specific surface area is large, resulting in increased side reactions between the negative electrode active material and the electrolyte during the battery charge and discharge cycle, which will reduce the battery's first coulombic efficiency and volume energy density; and when the particle size Dv50 of the silicon-carbon composite particles is large (for example, greater than 15μm), the average particle size of the silicon-carbon composite particles is large, and the migration distance of lithium ions in the negative electrode active material becomes longer, affecting the battery's rapid discharge capability.
[0088] In the present invention, the particle size Dv50 of the silicon-carbon composite particles can be measured by conventional methods in the art, such as a laser particle size test method, specifically as follows: using a Malvern particle size tester for measurement, the test steps are as follows: the silicon-carbon composite particles are dispersed in deionized water containing a dispersant (such as nonylphenol polyoxyethylene ether) (the mass content of the dispersant is 0.02%-0.03%), ultrasonicated for 2 minutes, and then placed in a Malvern particle size tester for testing.
[0089] In the present invention, the specific surface area of the silicon-carbon composite particles can be 0.2 m 2 / g-20m 2 / g, for example 0.2m 2 / g, 0.5m 2 / g, 1m 2 / g, 2m 2 / g, 3m 2 / g, 4m 2 / g, 5m 2 / g, 6m 2 / g, 7m 2 / g, 8m 2 / g, 9m 2 / g, 10m 2 / g, 11m 2 / g, 12m 2 / g, 13m 2 / g, 14m 2 / g, 15m 2 / g, 16m 2 / g, 17m 2 / g, 18m 2 / g, 19m 2 / g or 20m 2 / g.
[0090] In one example, the specific surface area of the silicon-carbon composite particles is 0.5 m 2 / g-10.3m 2 / g.
[0091] When the specific surface area of the silicon-carbon composite particles is small (e.g., less than 0.2 m 2 / g), the specific surface area of the silicon-carbon composite particles is too small. In the process of preparing the electrode sheet, the amount of binder that can be adsorbed on the surface of the negative electrode active material is small, which makes the negative electrode active material easy to fall off from the negative electrode sheet during the battery cycle, causing the battery capacity to decay; and when the specific surface area of the silicon-carbon composite particles is larger (for example, greater than 20m 2 / g), the specific surface area of the silicon-carbon composite particles is too large, resulting in more side reactions between the negative electrode active materials and the electrolyte, which will reduce the first coulombic efficiency and volume energy density of the battery.
[0092] In the present invention, the specific surface area of the silicon-carbon composite particles can be measured by conventional methods in the art, such as using a Tri Star II specific surface analyzer for measurement.
[0093] In the present invention, the negative electrode active material may further include a carbon-based material, which may include at least one of artificial graphite, natural graphite, mesophase carbon microbeads, soft carbon and hard carbon.
[0094] In the present invention, the mass ratio of the silicon-carbon composite particles to the carbon-based material may be 1:(0.01-50), for example, 1:0.01, 1:0.05, 1:0.1, 1:0.5, 1:1, 1:5, 1:10, 1:20, 1:30, 1:40 or 1:50.
[0095] In one example, the mass ratio of the silicon-carbon composite particles to the carbon-based material is 1:(0.1-19).
[0096] The present invention also provides a method for preparing the silicon-carbon composite particles, the method comprising at least the following steps:
[0097] The porous carbon material is placed in a vapor deposition device, N2 is introduced, and the temperature is increased to 300°C-500°C; monosilane gas is introduced for the first time, and then monosilane gas is introduced for the second time; the introduction of monosilane gas is stopped, the temperature is increased to 450°C-650°C, and acetylene gas is introduced.
[0098] In the present invention, the flow rate of N2 introduced is 100sccm-300sccm.
[0099] In the present invention, the flow rate of the first introduction is 10 sccm-200 sccm; the time of the first introduction is 20 min-300 min.
[0100] In the present invention, the flow rate of the second introduction is 50 sccm-300 sccm; the time of the first introduction is 20 min-300 min.
[0101] In the present invention, the flow rate of the acetylene gas is 50 sccm-200 sccm; the time of the acetylene gas is 5 min-240 min.
[0102] In the present invention, the preparation method further comprises pre-treating the porous carbon material and then placing it in the vapor deposition equipment.
[0103] In the present invention, the pretreatment may include soaking the porous carbon material with a solvent. The solvent may include at least one of nitric acid, sulfuric acid and phosphoric acid. The concentration of the solvent is, for example, 0.001 mol / L-0.05 mol / L. The soaking temperature may be 90°C-100°C. The soaking time may be 3h-60h.
[0104] In the present invention, the preparation method further comprises soaking and drying with a lithiated solvent after the acetylene gas is introduced. The lithiated solvent comprises, for example, a tetrahydrofuran solution of lithium biphenyl. The soaking time is, for example, 1 min to 60 min.
[0105] A second aspect of the present invention provides a negative electrode sheet, which comprises the negative electrode active material described in the first aspect of the present invention.
[0106] In the present invention, the negative electrode sheet may include a negative electrode current collector and a negative electrode active material layer located on at least one side of the negative electrode current collector. The negative electrode active material layer may include the negative electrode active material.
[0107] In the present invention, the negative electrode active material layer may further include a negative electrode conductive agent and a negative electrode binder. The negative electrode conductive agent may include at least one of conductive carbon black, acetylene black, Ketjen black, conductive graphite, carbon nanotubes (including at least one of single-walled carbon nanotubes and multi-walled carbon nanotubes) and carbon fibers. The negative electrode binder may include at least one of polyvinylidene fluoride (PVDF), sodium carboxymethyl cellulose, styrene-butadiene rubber, polytetrafluoroethylene, polyethylene oxide, polyacrylic acid and derivatives thereof.
[0108] In the present invention, based on the total mass of the negative electrode active material layer, the content of the negative electrode active material can be 80-99.8 weight % (for example, 80, 82, 84, 86, 88, 90, 92, 94, 96, 98, 99 or 99.8 weight %), the content of the negative electrode conductor can be 0.1-10 weight % (for example, 10, 9, 8, 7, 6, 5, 4, 3, 2, 1, 0.5 or 0.1 weight %), and the content of the negative electrode binder can be 0.1-10 weight % (for example, 10, 9, 8, 7, 6, 5, 4, 3, 2, 1, 0.5 or 0.1 weight %).
[0109] The third aspect of the present invention provides a battery, which may include the negative electrode active material described in the first aspect of the present invention and / or the negative electrode sheet described in the second aspect of the present invention.
[0110] In the present invention, the components of the battery other than the negative electrode sheet (such as the positive electrode sheet, the separator and the electrolyte) can be conventionally selected in the art.
[0111] In one example, the battery comprises a lithium-ion battery.
[0112] In one example, the battery includes a lithium-ion secondary battery.
[0113] It should be noted that the numerical expressions such as "first" and "second" in the present invention are only used to distinguish different substances or usages, and do not represent the difference in order.
[0114] The present invention will be described in detail below by way of examples. The examples described in the present invention are only a part of the examples of the present invention, rather than all of the examples. Based on the examples in the present invention, all other examples obtained by ordinary technicians in the field without creative work are within the scope of protection of the present invention.
[0115] In the following examples, unless otherwise specified, all materials used were commercially available analytical grade.
[0116] The following preparation examples are used to prepare the silicon-carbon composite particles of the present invention.
[0117] Preparation Example 1
[0118] Silicon-carbon composite particles were prepared as follows:
[0119] (1) Pretreatment of porous carbon: The porous carbon material (Dv10 is 4 μm, Dv50 is 9 μm, and Dv90 is 15 μm) is placed in a mixed solution of nitric acid, sulfuric acid, and phosphoric acid at a ratio of 1 g / 100 mL (the total concentration of nitric acid, sulfuric acid, and phosphoric acid is 0.01 mol / L), heated to 100 °C in a sealed container, immersed for 24 h, taken out, washed, and dried;
[0120] (2) Place the sample in a vapor deposition furnace, introduce 200 sccm N2, raise the temperature to 500°C, and then introduce monosilane gas at a flow rate of 100 sccm and 200 sccm for 2 hours each; then stop introducing monosilane, raise the temperature to 650°C, introduce acetylene gas at a flow rate of 100 sccm, and maintain for 1 hour;
[0121] (3) Soak in a tetrahydrofuran solution of 0.5 mol / L lithium biphenyl for 5 min and dry.
[0122] Preparation Example 2
[0123] (1) Pretreatment of porous carbon: The porous carbon material (Dv10 is 2 μm, Dv50 is 12 μm, and Dv90 is 20 μm) is placed in a mixed solution of nitric acid, sulfuric acid, and phosphoric acid at a ratio of 1 g / 100 mL (the total concentration of nitric acid, sulfuric acid, and phosphoric acid is 0.01 mol / L), heated to 100 °C in a sealed container, immersed for 10 h, taken out, washed, and dried;
[0124] (2) Place the sample in a vapor deposition furnace, introduce 200 sccm N2, raise the temperature to 500°C, then introduce monosilane gas at a flow rate of 100 sccm for 30 min and 200 sccm for 80 min; then stop introducing monosilane, raise the temperature to 650°C, introduce acetylene gas at a flow rate of 100 sccm, and maintain for 20 min;
[0125] (3) Soak in a tetrahydrofuran solution of 0.5 mol / L lithium biphenyl for 3 min and dry.
[0126] Preparation Example 3
[0127] (1) Pretreatment of porous carbon: The porous carbon material (Dv10 is 5 μm, Dv50 is 7 μm, and Dv90 is 12 μm) is placed in a mixed solution of nitric acid, sulfuric acid, and phosphoric acid at a ratio of 1 g / 100 mL (the total concentration of nitric acid, sulfuric acid, and phosphoric acid is 0.01 mol / L), heated to 100 °C in a sealed container, immersed for 36 h, taken out, washed, and dried;
[0128] (2) Place the sample in a vapor deposition furnace, introduce 200 sccm N2, raise the temperature to 500°C, and then introduce monosilane gas with a flow rate of 100 sccm and 200 sccm for 150 min each; then stop introducing monosilane, raise the temperature to 650°C, introduce acetylene gas with a flow rate of 100 sccm, and maintain for 120 min;
[0129] (3) Soak in a tetrahydrofuran solution of 0.5 mol / L lithium biphenyl for 10 min and dry.
[0130] Preparation Example 4
[0131] This group of preparation examples is used to verify the impact of changes in the "volume ratio of closed pores".
[0132] This group of examples was carried out with reference to Preparation Example 1, except that the volume percentage of closed pores was controlled by adjusting the time of introducing monosilane gas, as follows:
[0133] In preparation example 4a, monosilane gas was introduced at flow rates of 100 sccm and 200 sccm, respectively, for 180 min each;
[0134] In Preparation Example 4b, monosilane gas with a flow rate of 100 sccm for 25 min and 200 sccm for 60 min were introduced in sequence.
[0135] Preparation Example 5
[0136] This group of preparation examples is used to verify the influence of the change of "the thickness t of the shell".
[0137] This group of examples is carried out with reference to Preparation Example 1, except that the thickness t of the shell is controlled by adjusting the holding time of the acetylene gas, as follows:
[0138] Preparation Example 5a, acetylene gas was introduced at a flow rate of 100 sccm and maintained for 5 min;
[0139] In Preparation Example 5b, acetylene gas was introduced at a flow rate of 100 sccm and maintained for 200 min.
[0140] Preparation Example 6
[0141] This group of preparation examples is used to verify the impact of the change of "c2 / c1".
[0142] This group of examples was carried out with reference to Preparation Example 1, except that c2 / c1 was controlled by adjusting the time of introducing monosilane gas, as follows:
[0143] Preparation Example 6a, monosilane gas with a flow rate of 100 sccm for 150 min and 200 sccm for 90 min were introduced in sequence;
[0144] In Preparation Example 6b, monosilane gas with a flow rate of 100 sccm for 30 min and 200 sccm for 150 min were introduced in sequence.
[0145] Preparation Example 7
[0146] This group of preparation examples is used to verify the effects of changes in "nitrogen, phosphorus and sulfur elements in silicon-carbon composite particles".
[0147] This group of examples is carried out with reference to Preparation Example 1, except that the nitrogen, phosphorus and sulfur elements in the silicon-carbon composite particles are controlled by regulating the pretreatment of the porous carbon in step (1), as follows:
[0148] Preparation Example 7a, replacing the mixed solution with a sulfuric acid solution having a concentration of 0.01 mol / L;
[0149] In Preparation Example 7b, the porous carbon was not pretreated and step (2) was directly performed.
[0150] Preparation Example 8
[0151] This group of preparation examples is used to verify the impact of changes in the "sum of the contents of nitrogen, phosphorus and sulfur".
[0152] This group of examples was carried out with reference to Preparation Example 1, except that the sum of the contents of nitrogen, phosphorus and sulfur was controlled by adjusting the soaking time in step (1), as follows:
[0153] In Preparation Example 8a, the soaking time in step (1) is 3 h;
[0154] In Preparation Example 8b, the soaking time in step (1) is 60 h.
[0155] Preparation Example 9
[0156] Used to verify the impact of changes in "Silicon-carbon composite particles Dv90-Dv10".
[0157] The preparation was carried out in accordance with Preparation Example 1, except that the particle size of the silicon-carbon composite particles was controlled by regulating the particle size of the porous carbon. Specifically, the particle sizes of the porous carbon material were: Dv10 was 6 μm, Dv50 was 15 μm, and Dv90 was 30 μm.
[0158] Preparation Example 10
[0159] This group of preparation examples is used to verify the impact of changes in the "lithium content in silicon-carbon composite particles".
[0160] This group of preparation examples was carried out with reference to Preparation Example 1, except that the content of lithium in the silicon-carbon composite particles was controlled by regulating step (3), as follows:
[0161] In Example 10a, step (3) is not performed, i.e., the material obtained in step (2) is silicon-carbon composite particles;
[0162] In Example 10b, the soaking time in step (3) is 1 min;
[0163] In Example 10c, the soaking time in step (3) is 60 minutes.
[0164] The shell of the silicon-carbon composite particles prepared in the above preparation example includes amorphous carbon.
[0165] Comparative Preparation Example 1
[0166] The same method was followed as in Preparation Example 1, except that the temperature in step (2) and the flow rate and time of introducing monosilane were changed. Specifically, before introducing monosilane, the temperature was adjusted to 450°C, and then monosilane gas was introduced at a flow rate of 25 sccm for 16 h and 50 sccm for 4 h.
[0167] Comparative Preparation Example 2
[0168] The preparation was carried out in accordance with Preparation Example 1, except that the temperature in step (2) and the flow rate and time of introducing monosilane were changed. Specifically, before introducing monosilane, the temperature was adjusted to 550°C, and then monosilane gas was introduced at a flow rate of 200 sccm for 1 h and 400 sccm for 0.5 h.
[0169] Comparative Preparation Example 3
[0170] The process is carried out in accordance with Preparation Example 1, except that in step (2), after the introduction of monosilane is stopped, acetylene gas is not introduced and step (3) is directly carried out.
[0171] Comparative Preparation Example 4
[0172] The preparation was carried out in accordance with Preparation Example 1, except that the holding time of the acetylene gas was changed. Specifically, acetylene gas was introduced at a flow rate of 100 sccm and maintained for 300 min, wherein the thickness t of the shell was 15 nm.
[0173] Comparative Preparation Example 5
[0174] The preparation was carried out in accordance with Preparation Example 1, except that the time for introducing monosilane was changed. Specifically, 100 sccm of monosilane gas was introduced for 200 min and 200 sccm of monosilane gas was introduced for 80 min, respectively; wherein c1 was 40%, c2 was 60%, and c2 / c1 was 1.5.
[0175] Comparative Preparation Example 6
[0176] The preparation was carried out in accordance with Preparation Example 1, except that the time for introducing monosilane was changed. Specifically, 100 sccm of monosilane gas was introduced for 20 min and 200 sccm of monosilane gas was introduced for 80 min, respectively; wherein c1 was 40%, c2 was 5%, and c2 / c1 was 0.125.
[0177] The following examples are provided to illustrate the batteries of the present invention.
[0178] Example 1
[0179] Prepare as follows:
[0180] (1) Preparation of negative electrode sheet
[0181] Artificial graphite, the silicon-carbon composite particles prepared in Preparation Example 1, sodium carboxymethyl cellulose, styrene-butadiene rubber and SuperP were mixed in a mass ratio of 87.7:8.8:1.6:1.6:0.3, deionized water was added, and a negative electrode slurry was obtained under the action of a vacuum mixer; the negative electrode slurry was evenly coated on both sides of the copper foil, placed in an oven at 80°C and dried for 12 hours, and a negative electrode sheet was obtained after rolling and slitting.
[0182] (2) Preparation of positive electrode
[0183] Lithium cobalt oxide, polyvinylidene fluoride, acetylene black and carbon nanotubes are mixed in a mass ratio of 96:2:1.5:0.5, N-methylpyrrolidone is added, and stirred under the action of a vacuum mixer until a uniform positive electrode slurry is mixed; the positive electrode slurry is evenly coated on the surfaces of both sides of the aluminum foil, placed in an oven for baking, and then transferred to a 120°C oven for drying for 8 hours, and the positive electrode sheets are obtained after rolling and slitting.
[0184] (3) Preparation of lithium-ion batteries
[0185] The negative electrode sheet prepared in step (1), the separator (a polyethylene film with a thickness of 8 μm) and the positive electrode sheet prepared in step (2) are stacked in order, ensuring that the separator is located between the positive and negative electrode sheets to play an isolating role, and then a bare battery cell is obtained by winding; the bare battery cell is placed in an aluminum-plastic film shell, and an electrolyte (a mixed solution of lithium hexafluorophosphate dissolved in ethylene carbonate / dimethyl carbonate (volume ratio 1:1) and 5 vol.% fluoroethylene carbonate, wherein the concentration of lithium hexafluorophosphate is 1 mol / L) is injected into the dried bare battery cell, and a lithium ion battery is obtained through vacuum packaging, standing, forming, shaping, sorting and other processes.
[0186] (4) Preparation of button cells
[0187] The silicon-carbon composite particles prepared in Preparation Example 1, SuperP, sodium carboxymethyl cellulose and styrene-butadiene rubber were mixed in a mass ratio of 96.5:1.6:1.6:0.3, deionized water was added, and the mixture was mixed evenly under the action of a vacuum mixer to obtain a buckle-type negative electrode slurry; the buckle-type negative electrode slurry was coated on a copper foil, dried in an oven at 80°C, and then dried in a vacuum oven at 100°C for 12 hours to obtain a surface density of about 3 mg / cm 2 anode sheet; in a dry environment, the anode sheet was punched into anode discs with a diameter of 12 mm using a punching machine; in a glove box, the anode disc was used as a working electrode, the metal lithium sheet was used as a counter electrode, a polyethylene diaphragm with a thickness of 20 μm was used as an isolation membrane, and an electrolyte (a mixed solution of lithium hexafluorophosphate dissolved in ethylene carbonate / dimethyl carbonate (volume ratio 1:1) and 5 vol.% fluoroethylene carbonate, in which the concentration of lithium hexafluorophosphate was 1 mol / L) was added to assemble a button half-cell.
[0188] The groups of Examples 2 to 10 and Comparative Examples 1 to 6 were carried out with reference to Example 1, except that the silicon-carbon composite particles were prepared by replacing Preparation Example 1, as shown in Table 4 for details.
[0189] Example 11 Group
[0190] This group of examples is used to verify the impact of changes in the "mass ratio of silicon-carbon composite particles to carbon-based materials".
[0191] This group of examples is carried out with reference to Example 1, except that the mass ratio of the silicon-carbon composite particles and the artificial graphite is changed, as follows:
[0192] In Example 11a, artificial graphite, the silicon-carbon composite particles prepared in Preparation Example 1, sodium carboxymethyl cellulose, styrene-butadiene rubber and SuperP were mixed in a mass ratio of 8.8:87.7:1.6:1.6:0.3;
[0193] In Example 11b, artificial graphite, the silicon-carbon composite particles prepared in Preparation Example 1, sodium carboxymethyl cellulose, styrene-butadiene rubber and SuperP were mixed in a mass ratio of 91.7:4.8:1.6:1.6:0.3;
[0194] In Example 11c, artificial graphite, the silicon-carbon composite particles prepared in Preparation Example 1, sodium carboxymethyl cellulose, styrene-butadiene rubber and SuperP were mixed in a mass ratio of 94.6:1.9:1.6:1.6:0.3;
[0195] In Example 11d, the silicon-carbon composite particles prepared in Preparation Example 1, sodium carboxymethyl cellulose, styrene-butadiene rubber and SuperP were mixed in a mass ratio of 96.5:1.6:1.6:0.3.
[0196] Test Case I
[0197] (1) Determination of silicon content
[0198] The silicon content of the silicon-carbon composite particles prepared in the preparation example and the comparative preparation example was measured. First, the silicon-carbon composite particles were mixed with 6% polyacrylic acid solution in a mass ratio of 80:10 and then coated on the surface of copper foil. After drying, the mixed particles were processed with an argon ion cutter to obtain cross-sectional samples of the silicon-carbon composite particles. EDS was then used to measure the silicon content c1 in the first region and the silicon content c2 in the second region of the cross-section of the silicon-carbon composite particles, respectively. The mass content of silicon in the silicon-carbon composite particles was tested by thermogravimetric analysis. The results are recorded in Table 1.
[0199] (2) Determination of closed cell volume ratio
[0200] The closed pore volume of the silicon-carbon composite particles prepared in the preparation example and the comparative preparation example was measured, and the true density of the silicon-carbon composite particles was obtained by gas volume replacement method. The volume of the closed pores was then calculated, and the results are recorded in Table 1.
[0201] (3) Shell thickness measurement
[0202] The shell thickness of the silicon-carbon composite particles prepared in the preparation examples and the comparative preparation examples was measured, and the results are recorded in Table 1.
[0203] (4) Determination of element content
[0204] The silicon-carbon composite particles prepared in the preparation example were tested for element content. The contents of nitrogen and sulfur were determined using an element analyzer, and the contents of phosphorus and lithium were determined using ICP-AES. The results are recorded in Table 2.
[0205] (5) Particle size measurement
[0206] The particle size of the silicon-carbon composite particles prepared in the preparation example was measured, and the results were rounded and recorded in Table 2.
[0207] (6) Determination of oil absorption value
[0208] The silicon-carbon composite particles prepared in Preparation Example were subjected to oil absorption measurement, and the results are recorded in Table 3.
[0209] (7) Specific surface area determination
[0210] The specific surface area of the silicon-carbon composite particles prepared in Preparation Example was measured, and the results are shown in Table 3.
[0211] (8) Thermogravimetric test
[0212] The silicon-carbon composite particles prepared in the preparation example were subjected to thermogravimetric testing, and the results are recorded in Table 3.
[0213] (9) True density measurement
[0214] The true density of the silicon-carbon composite particles prepared in the preparation example was measured. The results showed that the true density of the silicon-carbon composite particles prepared in the preparation example and the comparative preparation example was 1.4 g / cm 3 -2.2g / cm 3 .
[0215] Table 1
[0216]
[0217]
[0218] Table 2
[0219]
[0220] Table 3
[0221] Oil absorption value (ml / 100g) <![CDATA[Specific surface area (m 2 / g)]]> 600℃-800℃ weight gain rate (%) Preparation Example 1 31 1.7 6.3 Preparation Example 2 79 10.3 0.5 Preparation Example 3 53 0.5 24.8 Preparation Example 4a 31 1.7 6.2 Preparation Example 4b 31 1.7 6.5 Preparation Example 5a 28 1.7 6 Preparation Example 5b 31 1.7 6.2 Preparation Example 6a 33 1.7 6.3 Preparation Example 6b 32 1.7 6.1 Preparation Example 7a 30 1.7 6 Preparation Example 7b 32 1.7 6.2 Preparation Example 8a 30 1.7 6.2 Preparation Example 8b 33 1.7 6.2 Preparation Example 9 20 1.1 6 Preparation Example 10a 31 1.7 6.2 Preparation Example 10b 30 1.7 6 Preparation Example 10c 32 1.7 6.3
[0222] Test Case II
[0223] (1) Cycle test
[0224] The lithium ion batteries prepared in the examples and comparative examples were subjected to cycle tests, and the specific test methods are as follows:
[0225] The battery was charged to 4.5V at a current density of 2C, then charged at a constant voltage of 4.5V with a cut-off current of 0.05C, and then left to stand for 10 minutes. The thickness of the battery at this time was recorded as the initial thickness; then discharged to 3.0V at a current density of 1.5C, and then left to stand for 10 minutes. The discharge capacity of the battery at this time was recorded as the initial capacity; the above charging and discharging process was repeated until the 500th cycle of constant voltage charging process was completed and left to stand for 10 minutes, and the thickness of the battery was tested and recorded as the thickness after the cycle, and then discharged to 3.0V at a current density of 1.5C, and left to stand for 10 minutes. The discharge capacity of the battery at this time was recorded as the capacity after the cycle. Then the cycle capacity retention rate = capacity after the cycle × 100% / initial capacity, thickness expansion rate = (thickness after the cycle - initial thickness) × 100% / initial thickness, and the cycle capacity retention rate and thickness expansion rate are recorded in Table 4.
[0226] (2) Energy density test
[0227] The lithium ion batteries prepared in the examples and comparative examples were subjected to energy density tests, and the specific test methods are as follows:
[0228] The battery was charged at a constant current of 0.2C to 4.5V, then charged at a constant voltage of 4.5V with a cut-off current of 0.02C. After standing for 10 minutes, it was discharged at a constant current of 0.2C to 3.0V and stood for 10 minutes. The first-cycle discharge capacity and first-cycle discharge energy of the battery were recorded. The battery was then charged at a constant current of 0.2C with a cut-off condition that the charging capacity reached half of the first-cycle discharge capacity. After the cut-off, the battery was removed and the thickness, length and width of the battery were measured. The energy density of the battery = first-cycle discharge energy / (length × width × thickness). The results are recorded in Table 4.
[0229] (3) Rapid discharge capability test
[0230] The lithium ion batteries prepared in the examples and comparative examples were tested for rapid discharge capability, and the specific test method is as follows:
[0231] The battery was charged at a constant current of 0.2C to 4.5V, then charged at a constant voltage of 4.5V with a cut-off current of 0.02C. After standing for 10 minutes, it was discharged to 3.0V at current densities of 0.2C and 1C respectively. The ratio of the capacity released at 1C to the capacity released at 0.2C is the rapid discharge capability of the battery. The results are recorded in Table 4.
[0232] (4) First Coulomb efficiency test
[0233] The button cells prepared in Examples 1-10 and the comparative example were subjected to the first coulombic efficiency test, and the specific test method is as follows:
[0234] After the battery was left to stand for 2 hours, it was discharged at a constant current density of 0.1C to 5mV. After standing for 10 minutes, it was discharged again at a current density of 0.01C to 5mV. After standing for another 10 minutes, it was charged at a constant current density of 0.05C to 1.5V. The first coulomb efficiency = charging capacity × 100% / discharge capacity. The results are recorded in Table 4.
[0235] (5) Ion diffusion coefficient test
[0236] After the battery has been allowed to stand for 2 hours, it is discharged at a constant current density of 0.1C to 5mV. After standing for 10 minutes, it is discharged at a current density of 0.01C to 5mV. After standing for 10 minutes again, it is charged to 1.5V at a current density of 0.05C. After standing for 10 minutes again, the process of discharging at a constant current density of 0.1C for 30 minutes and standing for 30 minutes is repeated until the battery voltage is lower than 0.1V. After standing for 30 minutes again, the voltage E1 at this time is recorded. Then, the battery is discharged at a constant current density of 0.1C for 30 minutes. The voltage E2 at 10s of discharge and the voltage E3 at the end of discharge are recorded. Then, it is allowed to stand for 60 minutes. The voltage E4 after standing for 60 minutes is recorded. According to the formula
[0237]
[0238] The silicon-carbon composite particles can be obtained at 0.1V (vs Li + The lithium ion diffusion coefficient (in cm) at the potential of 2 / s), where τ is the relaxation time, i.e., τ = 3600s; n is the molar number of silicon-carbon composite particles, V is the molar volume of silicon-carbon composite particles, and n×V is the volume of silicon-carbon composite particles used in the test, which can be calculated based on the mass w of the coating in the button battery negative electrode sheet and the true density ρ of the silicon-carbon composite particles, n×V = 0.965×w / ρ; S is the geometric area of the button battery negative electrode sheet, i.e., S = 1.13cm 2 , and record the results in Table 4.
[0239] Table 4
[0240]
[0241]
[0242] Note: Since the first coulombic efficiency and lithium ion diffusion coefficient were tested by button cells, the button cells of Example 11 were the same as those of Example 1, so the first coulombic efficiency and lithium ion diffusion coefficient were not tested for Example 11, and the “ / ” in Table 4 indicates that they were not tested.
[0243] It can be seen from Table 4 that the battery prepared by the negative electrode active material of the present invention can take into account higher energy density, first coulombic efficiency, rate performance and cycle stability compared with the comparative example.
[0244] The preferred embodiments of the present invention are described in detail above, but the present invention is not limited thereto. Within the technical concept of the present invention, the technical solution of the present invention can be subjected to a variety of simple modifications, including the combination of various technical features in any other suitable manner, and these simple modifications and combinations should also be regarded as the contents disclosed by the present invention and belong to the protection scope of the present invention.
Claims
1. A negative electrode active material, characterized in that: The negative electrode active material includes silicon-carbon composite particles; The silicon-carbon composite particles have closed pores, and the volume ratio of the closed pores is 4%-50%; The silicon-carbon composite particles have a core-shell structure, the shell of the core-shell structure includes carbon element, and the thickness of the shell is t, where 0 < t ≤ 10 nm; On the cross-section of the silicon-carbon composite particles, there are a first region and a second region. The content of silicon element in the first region is c1, and the content of silicon element in the second region is c2, where 0.15 ≤ c2 / c1 ≤ 1.4; wherein, the dimension of the perpendicular line of the tangent at any point on the edge of the cross-section on the cross-section is L. On the perpendicular line, the region at a distance of 0.001L - 0.1L from the edge of the cross-section constitutes the first region, and the region at a distance of 0.1L - 0.5L from the edge of the cross-section constitutes the second region.
2. The negative electrode active material according to claim 1, wherein 0.15 < c2 / c1 ≤ 1.25; preferably, 0.23 < c2 / c1 ≤ 0.76; And / or, the volume ratio of the closed pores is 5%-49%; preferably 11%-35%; And / or, 0.2 nm ≤ t ≤ 10 nm; preferably, 1 nm ≤ t ≤ 8 nm.
3. The negative electrode active material according to claim 1 or 2, wherein The mass content of silicon element in the silicon-carbon composite particles is 20%-65%; preferably 21%-64%; more preferably 25%-60%; And / or, the content c1 of silicon element in the first region is 30%-75%; preferably 31%-71%; more preferably 38%-66%; And / or, the content c2 of silicon element in the second region is 5%-60%; preferably 6%-55%; more preferably 9%-50%.
4. The negative electrode active material according to claim 1 or 2, wherein The core of the core-shell structure includes carbon element and silicon element; Preferably, the core includes porous carbon and silicon material located in the pores of the porous carbon; Preferably, the shell includes amorphous carbon.
5. The negative electrode active material according to claim 1 or 2, wherein: The silicon-carbon composite particles include at least one of nitrogen element, phosphorus element and sulfur element; Preferably, the silicon-carbon composite particles include nitrogen element, phosphorus element and sulfur element; More preferably, the sum of the contents of nitrogen element, phosphorus element and sulfur element in the silicon-carbon composite particles is 15 ppm - 1000 ppm; preferably 30 ppm - 500 ppm.
6. The negative electrode active material according to claim 1 or 2, wherein: The particle sizes Dv90 and Dv10 of the silicon-carbon composite particles satisfy 5 μm ≤ Dv90 - Dv10 ≤ 25 μm; preferably, 7 μm ≤ Dv90 - Dv10 ≤ 24 μm; more preferably, 7 μm ≤ Dv90 - Dv10 ≤ 18 μm; And / or, Dv10 is 1 μm - 6 μm; preferably 2 μm - 5 μm; And / or, Dv90 is 10 μm - 30 μm; preferably 12 μm - 20 μm.
7. The negative electrode active material according to claim 1 or 2, wherein: The oil absorption value of the silicon-carbon composite particles is 10 ml / 100 g - 100 ml / 100 g; Preferably, the oil absorption value of the silicon-carbon composite particles is 31 ml / 100 g - 79 ml / 100 g.
8. The negative electrode active material according to claim 1 or 2, wherein The silicon-carbon composite particles include lithium element; Preferably, the content of lithium element in the silicon-carbon composite particles is 0.1%-20%; More preferably, the content of lithium element in the silicon-carbon composite particles is 1%-5%.
9. The negative electrode active material according to claim 1 or 2, wherein: The thermogravimetric curve of the silicon-carbon composite particles in air atmosphere has a weight gain peak at 600° C.-800° C.; Preferably, the thermogravimetric curve of the silicon-carbon composite particles in air atmosphere has a weight gain rate of 0.1%-40% at 600°C-800°C; More preferably, the thermogravimetric curve of the silicon-carbon composite particles in an air atmosphere has a weight gain rate of 0.5% to 24.8% at 600° C. to 800° C.
10. The negative electrode active material according to claim 1 or 2, wherein The true density of the silicon-carbon composite particles is 1.4 g / cm 3 -2.2g / cm 3 ; And / or, the particle size Dv50 of the silicon-carbon composite particles is 6 μm-15 μm; preferably 7 μm-12 μm; And / or, the specific surface area of the silicon-carbon composite particles is 0.2 m 2 / g-20m 2 / g; preferably 0.5m 2 / g-10.3m 2 / g.
11. A negative electrode sheet, characterized in that: The negative electrode sheet comprises the negative electrode active material according to any one of claims 1 to 10.
12. A battery, characterized in that: The battery comprises the negative electrode active material according to any one of claims 1 to 10 and / or the negative electrode sheet according to claim 11.
Citation Information
Patent Citations
Anode active material and lithium secondary battery comprising same
CN107851780A
Silicon-carbon composite material, preparation method thereof and secondary battery
CN115732664A
Negative electrode material, negative electrode plate and battery
CN116053447A
High performance silicon-based materials for lithium ion battery anodes
CN116057726A
Silicon-based negative electrode material, silicon electrode and lithium ion battery
CN116230885A
Cited By
Battery cell, battery device, and electric device
CN122337996A
Silicon-carbon composite material, preparation method therefor, secondary battery and electronic apparatus
WO2026207693A1